Consumption Corridors and the Case of Meat - M. Kanerva (Journal of Consumer Policy, 2022)
Consumer policy must address the unsustainability of consumption which now threatens consumer safety in the form of the climate and ecological crises. Arguably, only strong sustainable consumption governance methods can bring about changes at the scale and speed required. This article discusses one emerging policy tool within strong governance, namely consumption corridors which could bring about absolute reductions in the negative impacts of consumption in a just manner and using deliberative democracy. Consumption corridors are applied in the context of the current meat system, a common driver for the twin crises, and an issue central to achieving the sustainable development, biodiversity, and Paris climate goals. The recently developed planetary health diet offers a useful plan for the transformation of global food systems, and could be combined with sustainable consumption corridors for meat. Systems thinking identifies change in societal paradigms as most effective. To support such change, this article suggests two metaphors as discourse tools, whereby individual and societal transformation in meat consumption occurs as a journey along a continuum of different meatways. The article also suggests specific actions for bringing about meat consumption corridors, and argues that this context could also serve as a bridge for increased societal acceptance of recomposed consumption.
Keywords: 650; Climate crisis; Ecological crisis; Strong sustainable consumption governance; Planetary health diet; Consumption corridors; New meatways